Mobile-Based Interactive Multimedia Learning for Problem-Solving Skills in Vocational High School - Aurum, Emma Valensia; Surjono, Herman Dwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This research aims to solve some common problems faced by learners, namely difficulties in understanding materials with abstract ideas and the lack of problem-solving skills. Mobile-based interactive learning multimedia as an innovation in educational setting is a self-learning media that the learners can use both in school and at home to help them understand the materials easily, minimize learning difficulties, and increase their problem-solving skills. This is a Research and Development (R&D) with the APPED model. The subjects of this research were the 10th grade students of the Vocational Program of Computer and Network Technology at SMK Negeri 1 Tulung Klaten (State Vocational School 1 of Tulung, Klaten). The data analysis technique was done through the descriptive quantitative. The results showed that the mobile-based interactive multimedia learning was feasible with the Very Good category. The mobile-learning-based interactive multimedia learning was effectively used with a percentage of 77.85% and the difference in significance, based on the Wilcoxon Test on the pretest posttest of 0.000 it indicates that there is a difference in the increase in problem-solving skills while learning using the mobile-based interactive multimedia learning.